Technological progress for sustaining food-population balance: achievement and challenges - Hossain, Mahabub (Wiley, 2007)
The growth in land productivity in rice cultivation has slowed down substantially since the early 1990s due to technological progress reaching its limit in the irrigated ecosystem and nonavailability of suitable technologies for the unfavorable rainfed environments. This development raises concern regarding the world's ability to meet the food‐population balance in the coming decades. Rice research must deal with a number of difficult problems to meet the challenge: raising the yield ceilings of the current available rice varieties; protecting the past yield gains in the irrigated ecosystem; and using biotechnology tools to develop high yielding varieties for the rainfed systems that are tolerant to drought, submergence, and problem soils. The speed and extent of meeting these challenges depends on the level of resources that can be mobilized to support crop improvement research in the public sector.